The safety and effectiveness of open-label extended-release carbamazepine in the treatment of children and adolescents with bipolar I disorder suffering from a manic or mixed episode - Findling RL (Dove Medical Press, 2014)
Robert L Findling,1,2 Lawrence D Ginsberg31Division of Child and Adolescent Psychiatry, Department of Psychiatry and Behavioral Sciences, Johns Hopkins University, 2Kennedy Krieger Institute, Baltimore, MD, USA; 3Red Oak Psychiatry Associates, PA, Houston, TX, USAObjective: To assess the safety and effectiveness of open-label treatment with extended-release carbamazepine (ERC) in pediatric subjects suffering from bipolar I disorder.Method: Medically healthy youths aged 10–17 years suffering from an acute manic or mixed episode were eligible. After screening for study eligibility, the youths began a 5-week titration period in which doses of ERC were adjusted in order to optimize benefit whilst minimizing adverse events, at doses between 200–1,200 mg/day. Thereafter, subjects could continue to receive treatment during a subsequent 21-week period. Safety measures included spontaneously reported adverse events (AEs) and laboratory assessments. The primary efficacy measure was the Young Mania Rating Scale (YMRS).Results: A total of 60 children (ages 10–12) and 97 adolescents (ages 13–17), with an overall average age of 13.4 years (standard deviation [SD] 2.0 years) received ERC. The mean duration of study participation was 109.6 days (SD 70.2 days), with 66 (42%) completing the entire study. At end of study participation (end point), the most prevalent dose of ERC was 1,200 mg: 31.7% of children and 24.7% of adolescents reached the 1,200 mg dose. The YMRS decreased from a mean of 28.6 (SD 6.2) at baseline to a mean of 13.8 (SD 9.4) (P<0.0001) at end point. A total of 26 subjects discontinued study participation because of AEs, the most common of which were rash (n=6), white blood cell count decreased (n=5), nausea (n=3), and vomiting (n=3). No deaths were reported. The most commonly reported AEs were headache (n=41), somnolence (n=30), nausea (n=22), dizziness (n=21), and fatigue (n=19).Conclusions: Open-label administration of ERC might be a safe and effective intervention in this subject population. More definitive studies are warranted.Keywords: bipolar disorder, children, adolescents, treatment, carbamazepine